Ethylazinphos Interaction with Membrane Lipid Organization Induces Increase of Proton Permeability and Impairment of Mitochondrial Bioenergetic Functions - Videira, Romeu A. (2001)
Ethylazinphos increases the passive proton permeability of lipid bilayers reconstituted with dipalmitoylphosphatidylcholine (DPPC) and mitochondrial lipids. A sharp increase of proton permeability is detected at insecticide/lipid molar ratios identical to those inducing phase separation in the plane of DPPC bilayers, as revealed by differential scanning calorimetry (DSC). Ethylazinphos progressively depresses the transmembrane potential ([Delta][Psi]) of mitochondria supported by piruvate/malate, succinate, or ascorbate/TMPD. Additionally, a decreased depolarization induced by ADP depends on ethylazinphos concentration, reflecting a phosphorylation depression. This loss of phosphorylation is a consequence of a decreased [Delta][Psi]. A decreased respiratory control ratio is also observed, since ethylazinphos stimulates state 4 respiration and inhibits ADP-stimulated respiration (state 3). Ethylazinphos concentrations up to 100 nmol/mg mitochondrial protein increase the rate of state 4 together with a decrease in [Delta][Psi], without significant perturbation of state 3 and carbonyl cyanide-p-trifluoromethoxyphenylhydrazone (FCCP)-uncoupled respiration. For increased insecticide concentrations, the state 3 and FCCP-uncoupled respiration are inhibited to approximately the same extent. The perturbations are more pronounced when the energization is supported by pyruvate/malate and less effective when succinate is used as substrate. The present data, in association with previous DSC studies, indicate that ethylazinphos, at concentrations up to 100 nmol/mg mitochondrial protein, interacts with the lipid bilayer of mitochondrial membrane, changing the lipid organization and increasing the proton permeability of the inner membrane. The increased proton permeability explains the decreased oxidative phosphorylation coupling. Resulting disturbed ATP synthesis may significantly underlie the mechanisms of ethylazinphos toxicity, since most of cell energy in eukaryotes is provided by mitochondria.